Utak és lehetőségek Pozsony és Sopron líceumának összehasonlító elemzése - Dulovics, Alex (Gerundium, 2017)
Ways and possibilities in the analytical comparison of lycea of Bratislava and Sopron. In 1781 Joseph the II’ Edict of Tolerance has opened a new age in the life of the protestants’ educational system. After its introduction radical alterations took place in these institutions. Guarded by the law these schools started to expand and modernize their higher educational environments. On one hand I would like to briefly summarize these processes until 1849. On the other hand, I wish to present all the information we collectedabout their students from this period.